Wnt8a and Wnt3a cooperate in the axial stem cell niche to promote mammalian body axis extension. Issue 6 (23rd April 2015) - Cunningham, Thomas J.; Kumar, Sandeep; Yamaguchi, Terry P.; Duester, Gregg
Abstract : Background: Vertebrate body axis extension occurs in a head‐to‐tail direction from a caudal progenitor zone that responds to interacting signals. Wnt/β‐catenin signaling is critical for generation of paraxial mesoderm, somite formation, and maintenance of the axial stem cell pool. Body axis extension requires Wnt8a in lower vertebrates, but in mammals Wnt3a is required, although the anterior trunk develops in the absence of Wnt3a .Results: We examined mouse Wnt8a –/– and Wnt3a –/– single and double mutants to explore whether mammalian Wnt8a contributes to body axis extension and to determine whether a posterior growth function for Wnt8a is conserved throughout the vertebrate lineage. We find that caudal Wnt8a is expressed only during early somite stages and is required for normal development of the anterior trunk in the absence of Wnt3a . During this time, we show that Wnt8a and Wnt3a cooperate to maintain Fgf8 expression and prevent premature Sox2 up‐regulation in the axial stem cell niche, critical for posterior growth. Similar to Fgf8, Wnt8a requires retinoic acid (RA) signaling to restrict its caudal expression boundary and possesses an upstream RA response element that binds RA receptors.Conclusions: These findings provide new insight into interaction of caudal Wnt‐FGF‐RA signals required for body axis extension. Developmental Dynamics 244:797–807, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: Wnt8a and Wnt3a exhibit overlapping functions during the early stage of body axis extension. Wnt8a‐/‐ embryos do not exhibit body axis extension defects. Wnt8a/Wnt3a double knockouts cease body axis extension earlier than Wnt3a mutants correlating with early termination of caudal Fgf8 expression and ectopic Sox2 expression. Embryo ChIP identified an RA response element associated with RA repression of caudal Wnt8a expression. Our findings provide new insight into how Wnt‐FGF‐RA signals interact during body axis extension.